SOLIDWORKS: Surfacing. - Corbett, Gabriel (linkedin.com, 2015)
Get up to speed with the surfacing tools within SOLIDWORKS fast. Learn how to create and modify surfaces, troubleshoot common issues, and manipulate faces in surfaces and solids.